2005
DOI: 10.3109/10929080500229447
|View full text |Cite
|
Sign up to set email alerts
|

How does soft tissue distribution affect anteversion accuracy of the palpation procedure in image-free acetabular cup navigation? An ultrasonographic assessment

Abstract: Navigation of the acetabular cup in total hip replacement (THR) is used to improve the reproducibility of acetabular component positioning. When the palpation of anatomic landmarks, which is necessary to determine the pelvic coordinate system, is performed epicutaneously, the question as to how uneven soft tissue distribution can influence navigation accuracy arises. To obtain data, the questionable soft tissue thickness was measured in 72 patients scheduled for THR. In addition, distances between the landmark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 16 publications
0
17
2
1
Order By: Relevance
“…Richolt et al [41] used ultrasonographic measurements to determine the minimal soft tissue thickness between skin surfaces and bony landmarks in 72 patients. Soft tissue thickness over the anterosuperior iliac spines averaged 7.9 ± 3.4 mm and 13.6 ± 4.1 mm over the pubic tubercles (5.7 ± 3.4 mm thicker than the iliac spines).…”
Section: The Anterior Pelvic Planementioning
confidence: 99%
“…Richolt et al [41] used ultrasonographic measurements to determine the minimal soft tissue thickness between skin surfaces and bony landmarks in 72 patients. Soft tissue thickness over the anterosuperior iliac spines averaged 7.9 ± 3.4 mm and 13.6 ± 4.1 mm over the pubic tubercles (5.7 ± 3.4 mm thicker than the iliac spines).…”
Section: The Anterior Pelvic Planementioning
confidence: 99%
“…We did not address the issue of inter-observer variation, and a second study has been designed to control for this specific aspect. We also made no attempt to measure the thickness of the fat tissue, which would enable our results to be compared to those from a previously published study [12]; however, the small range of variation observed in our study leads us to believe that this factor may have less importance than expected.…”
Section: Discussionmentioning
confidence: 92%
“…Cutaneous palpation of the pelvic anatomic landmarks might be inaccurate because of the distance between the skin surface and the real bone contour. Richolt et al [12] calculated that the mean error in the measurement of flexion of the pelvis was 3 because of the thickness of the soft tissue. Furthermore, there might be inaccuracy in defining the actual top of the ASIS.…”
Section: Discussionmentioning
confidence: 99%
“…This registration method is very convenient but might not always be that accurate in a real surgery due to an unknown amount of soft tissue between the bone and the skin surface. The unknown amount of soft tissue is not an error specific to our application as it is a general source of error also for optical navigation-based system that use palpation to digitize landmarks [27]. In our plastic bone study, this problem is not apparent since we can directly place the device onto the necessary bony structures.…”
Section: Discussionmentioning
confidence: 95%